Basic Design of A Charging Circuit for Mobile Phone Using Solar Panel - Lianly Rompis; Julie Rante (SISFORMA, 2018)
Currently the learning process cannot be separated from the exchange of digital information and online interaction. Initially using computer technology and internet, then growing with the existence of mobile phone technology. The demand of Digital Learning for efficient and environmentally friendly energy is very important and urgent because of the increasingly expensive price of fuel and the high utilization of mobile phones as a learning tool for the society. Our government itself supports the discoveries, researches, and technologies that use renewable energy such as energy from sunlight and biomass energy. The city of Manado which located in North Sulawesi province has a good hot climate every year and a fairly high solar energy. This is very good if it can be used as a source of energy for certain equipment such as mobile phones. This paper describes a basic research that has been done where the energy of sunlight becomes alternative energy to charge a mobile phone. The research method is literature study, theory comparison, block diagram design, assembly, and testing. The results obtained give hope that in the future there are opportunities to develop further research and design a solar energy source for mobile phones charging, by using solar cells that have specific current and voltage specification.